Factor Affecting Strategic Plan Implementation: A Case Study of Commercial Bank of Ethiopia Head Office - Asamnew T, Bekele; Abebe, Getachew Tareke; Ayele, Waganeh Wassie (Syntax Corporation, 2024)
This study examines the factors affecting strategic plan implementation in case of commercial bank of Ethiopia. The research design was an explanatory, quantitative study that examined the factors associated with the successful implementation of strategic plans within Commercial Bank of Ethiopia. Using a judgmental sampling technique, the analysis was conducted on a sample size of 196. The findings revealed that several organizational enablers had a significant positive relationship with strategic plan implementation (SPI). The strongest predictor of SPI was effective communication, underscoring the critical role of clear, consistent, and transparent communication from leadership in driving strategy execution. Stakeholder engagement, leadership support, and the alignment of human resources practices with strategic priorities also emerged as key drivers of successful SPI. Interestingly, the study did not find a significant relationship between resource availability and SPI, challenging the common assumption that a lack of resources is a primary barrier to strategy implementation. These findings emphasize the importance of developing organizational capabilities, such as communication, stakeholder management, and HR-strategy alignment, to enhance the effective translation of strategic plans into tangible outcomes. The study provides valuable insights for organizations seeking to bridge the strategy-to-execution gap and improve the implementation of their strategic initiatives. By focusing on cultivating these organizational enablers, particularly effective leadership communication, organizations can more successfully drive the execution of their strategic plans and achieve their desired outcomes.